The Behavioral Intention of Blockchain Adoption - Purusottama, Ambara; Sunitiyoso, Yos; Simatupang, Togar Mangihut; Fuadah, Puteri Annisa Tsamrotul (JDM (Jurnal Dinamika Manajemen), 2023)
Despite the growing urgency, discussions about the diffusion of this technology are still challenging to identify and understand. This study attempts to investigate further the intention of blockchain adoption in society. This study used a survey strategy and was analysed using structural equation modelling. Furthermore, this study collected 96 respondents using a purposive sampling technique. The findings show that a few hypotheses diverged from the developed model. Blockchain adoption is suitable for today's problems and has a relative advantage over other technologies in influencing individual perceptions. However, the limited knowledge of society makes blockchain adoption only focused on a particular context. The role of the social environment is more visible in its significance on the intention to adopt blockchain technology along with individual perceptions. The research model attempted to extend the existing technology adoption behaviour theory widely used to understand technological adoption.